الحذف في ترجمة دبلجة الفيلم السينمائي "أسد الصحراء" عمر المختار Omission in the dubbing of the movie “Lion of the desert” ʿUmar Al-Mukhtār - Ali, Asem Shehadeh Saleh; Ibrahim, Omnia Aḥmad Abdul Wanis (IIUM, 2021)
يهدف هذا البحث إلى تسليط الضوء على الدبلجة التي تصنف ضمن الأنواع الأكثر شهرةً بين أنواع الترجمة السمعية البصرية، والتي يقصد بها تركيب صوت جديد على الصوت القديم؛ سواء كان بلغة مختلفة أم باللغة نفسها؛ على أن يتم ذلك وفق شروط تتعلق بضرورة المحافظة على طول الجمل والمدة التي يستغرقها النطق بها، ومزامنة الكلام الجديد مع حركات شفاه المتكلمين الأصليين. واعتمد البحث في جانبه التطبيقي على فيلم "أسد الصحراء" الذي أنتج بالإنجليزية ودبلج إلى العربية بعنوان (عمر المختار). ومن خلال المنهج الوصفي التحليلي قدم الباحثان وصفاً نظرياً لظاهرة الدبلجة، ولأسلوب الحذف في الترجمة، وانتقيا (6) نماذج للحذف على مستوى الكلمة وردت في الفيلم على لسان أبطاله، وتناولا دبلجتها بالتحليل لتحديد ما إذا كانت عمليات الحذف تؤدي في النهاية إلى نقل المعنى المراد من النص الأصلي، وإلى تحقق التزامن بين الصوت والصورة. وقد تبين من الدراسة أن عمليات الحذف التي أُجريت لم تغير في الواقع من المحتوى الكلي للرسالة التي يتضمنها النص الأصلي، ولم تضف إلى محتواها الدلالي؛ وإنما أسهمت في نقل المعاني، وإيصال المعلومات إلى لغة المتلقي بأسلوب أوضح، كما تبين أن مبدأ التزامن قد تحقق في معظم النماذج التي تم تحليلها؛ فجاءت العبارات المدبلجة متزامنة في المدة التي قيلت فيها مع العبارات الأصلية، ومتسقة مع حركات شفاه الممثلين، وإشاراتهم الجسدية. الكلمات المفتاحية: الحذف، الترجمة، الدبلجة، الفيلم السينمائي، فيلم أسد الصحراء. This paper aims at highlighting on the dubbing process that is categorized as one of the most popular types of the audio-visual translation. It is a process of substituting the original script with the new voice either with a different language or with the same source text. Dubbing needs to preserve the length of the sentences and the time needed to complete the expression. It needs also to be synchronized with the movements of the lips of the original actors. The study focuses on the film ‘Lion of the desert’ which was originally produced in English and translated into Arabic with the new title ʿŪmar Mukhtār. Through descriptive analytical study the two writers present a theoretical description for dubbing and the method of omission in translation. 6 samples were extracted on the levels of words spoken by the original actors. They were analyzed to determine whether the dubbing manage to translate the original intended meaning or not and whether the synchronization between the visual and audio. It is observed from the study that the omissions that were done did not change the content of the original texts and the synchronization between the visual and the audio. It did not add new things to its semantic content. Rather, it helps to convey the content in a clearer manner. Synchronization was also achieved in most of the samples that were analyzed. The dubbed expressions were synchronous with the original script and movements of the lips of the actors as well as their body language. Keywords: Omission, Translation, Dubbing, Cinematic film, Lion of the Desert.